Metastasis to the Male Breast from Squamous Cell Lung Carcinoma - Berhan Genç; Aynur Solak; Neslin Şahin; Aşkın Gülşen (Case Reports in Oncological Medicine)
Metastasis to breast from extra mammarian organs is quite rare with an incidence of 0.5–3%. Malignancies that most commonly metastasize to breast are lymphomas, leukemias, and malignant melanoma. Metastasis of lung cancer to breast is a very rare condition. We present here a case with squamous cell lung cancer that metastasized to breast. A 65-year-old man presented with cough in addition to a mass in the left breast, which had been noted 3 weeks ago and grown gradually since then. A histopathological diagnosis of metastasis of squamous lung cancer was made for the mass in the left breast. PET/CT scan showed no distant metastasis. Chemoradiation therapy was applied for lung cancer. As the prognosis of such patients is extremely poor, it is of a great importance to distinguish a primary breast cancer from a metastatic breast lesion in order to determine the appropriate treatment modality.